1991
DOI: 10.1128/aem.57.1.146-150.1991
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of zearalenone sulfate produced by Fusarium spp

Abstract: A water-soluble compound related to zearalenone was isolated from a culture of Fusarium graminearum 30 grown in rice. The structure of the novel metabolite was determined to be zearalenone-4-sulfate on the basis of fast-atom-bombardment mass spectrometry, proton nuclear magnetic resonance, UV spectroscopy, and by chemical and enzymatic reactions. Strains representing Fusarium equiseti, Fusarium sambucinum, and Fusarium roseum produced the sulfate conjugate as well. In the rat uterus enlargement bioassay, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 24 publications
(16 reference statements)
4
60
0
Order By: Relevance
“…They comprise glucose and and sulphate conjugates of zearalenone and are known as 'masked' mycotoxins because they are not detected by the usual methods of analysis for zearalenone and its main metabolites. Such conjugates can be enzymatically cleaved to zearalenone in the GI tract of mammals such as pigs and rats (Gareis et al, 1990;Plasencia and Mirocha, 1991) and may therefore contribute to exposure to oestrogenically active substances from contaminated food and feed. It is not yet known with what frequency and at what concentrations such plant-specific metabolites may be present in contaminated food and feed.…”
Section: Toxicity In Animalsmentioning
confidence: 99%
“…They comprise glucose and and sulphate conjugates of zearalenone and are known as 'masked' mycotoxins because they are not detected by the usual methods of analysis for zearalenone and its main metabolites. Such conjugates can be enzymatically cleaved to zearalenone in the GI tract of mammals such as pigs and rats (Gareis et al, 1990;Plasencia and Mirocha, 1991) and may therefore contribute to exposure to oestrogenically active substances from contaminated food and feed. It is not yet known with what frequency and at what concentrations such plant-specific metabolites may be present in contaminated food and feed.…”
Section: Toxicity In Animalsmentioning
confidence: 99%
“…The formation of water soluble metabolites [40] or the conversion to zearalenone-glycosides induced by cooccurring Rhizopus fungi [41] frequently enhances the occurrence of masked mycotoxins. Degradation or inactivation of ZEA can mainly be achieved by application of chemical compounds like clay, activated carbon, montmorillonite or mannanoligosaccharides.…”
Section: Zea Biotransformationmentioning
confidence: 99%
“…Zearalenone (ZEN), a b-resorcylic acid lactone, is produced by several species of Fusarium, including Fusarium graminearum and Fusarium crookwellense (Di Menna et al, 1991;Plasencia & Mirocha, 1991), which infests grain cereals such as maize and wheat (Schollenberger et al, 2006). The infected host plant as well as other fungal species can transform ZEN into different conjugated forms which are primarily sulfate and glucoside esters.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the metabolism of ZEN by Rhizopus and Thamnidium species have shown the formation of ZEN-14-Glc and ZEN-14,16-O-b-diglucoside (Kamimura, 1986;El-Sharkawy, 1989). ZEN-14sulfate (ZEN-14-S) was found to be a natural metabolite of Fusarium graminearum, Rhizopus arrhizus, and Aspergillus niger (El-Sharkawy et al, 1991;Plasencia & Mirocha, 1991;Jard et al, 2010).…”
Section: Introductionmentioning
confidence: 99%